Water chemistry of Lagrangian samplings of Inland Elbe 2024 (MOSES Hydrological Extremes) - Norbert Kamjunke; Wolf von Tümpling; Andrea Hoff; Matthias Koschorreck (PANGAEA, 2025)
Within the framework of MOSES (Modular Observation Solutions for Earth Systems) and ElbeXtreme, we performed three longitudinal sampling campaigns in the Elbe catchment in 2024. The campaigns covered the German freshwater part, the tidal Elbe river, and the German Bight. Here we present the results of the freshwater river where the sampling was conducted in a Langrangian way according to flow velocity. Physico-chemical and biological parameters were measured along the Elbe from bridges between Bad Schandau (km 12, Czech-German border) and Lauenburg (km 570, close to Hamburg). A particular scientific focus was on (1) nutrients and eutrophication, (2) composition of dissolved organic matter measured by high-resolution mass spectrometry, (3) greenhouse gas measurements, and (4) micropollutants. This was done during a winter flood event in January, a summer drought in July, and a second smaller flood in September 2024.